Emotions and Public Policies - Coelho, Maria Claudia; Beleli, Iara (Antropologia, 2023)
The political moment experienced today by so many countries is marked by an intense polarization that intensifies the emotional dimension of political life, bringing feelings such as fear, hate, sympathy, shame and humiliation, among others, to the forefront. The formulation of public policies is one of the arenas in which divergent worldviews clash - a clash that is permeated by emotions. This pervasiveness of emotions attests to the undeniable urgency of turning the anthropological gaze to the role they play in politics. This volume intends to contribute to this effort by taking public policies (their formulation, their reception, their impact) as its objects.